Community‐Wide Dissemination of Bystander Cardiopulmonary Resuscitation and Automated External Defibrillator Use Using a 45‐Minute Chest Compression–Only Cardiopulmonary Resuscitation Training. Issue 1 (8th January 2019) - Nishiyama, Chika; Kitamura, Tetsuhisa; Sakai, Tomohiko; Murakami, Yukiko; Shimamoto, Tomonari; Kawamura, Takashi; Yonezawa, Takahiro; Nakai, Shohei; Marukawa, Seishiro; Sakamoto, Tetsuya; Iwami, Taku
Abstract : Background: Little is known about whether cardiopulmonary resuscitation (CPR) training can increase bystander CPR in the community or the appropriate target number of CPR trainings. Herein, we aimed to demonstrate community‐wide aggressive dissemination of CPR training and evaluate temporal trends in bystander CPR. Methods and Results: We provided CPR training (45‐minute chest compression–only CPR plus automated external defibrillator use training or the conventional CPR training), targeting 16% of residents. All emergency medical service–treated out‐of‐hospital cardiac arrests of medical origin were included. Data on patients experiencing out‐of‐hospital cardiac arrest and bystander CPR quality were prospectively collected from September 2010 to December 2015. The primary outcome was the proportion of high‐quality bystander CPR. During the study period, 57 173 residents (14.7%) completed the chest compression–only CPR training and 32 423 (8.3%) completed conventional CPR training. The proportion of bystander CPR performed did not change (from 43.3% in 2010 to 42.0% in 2015; P for trend=0.915), but the proportion of high‐quality bystander CPR delivery increased from 11.7% in 2010 to 20.7% in 2015 ( P for trend=0.015). The 1‐year increment was associated with high‐quality bystander CPR (adjusted odds ratio, 1.461; 95% CI, 1.055–2.024). Bystanders who previously experienced CPR training were 3.432 times (95% CI, 1.170–10.071) more likely to perform high‐quality CPR than those who did not. Conclusions: We trained 23.0% of the residents in the medium‐sized city of Osaka, Japan, and demonstrated that the proportion of high‐quality CPR performed on the scene increased gradually, whereas that of bystander CPR delivered overall remained stable.